MACHINE LEARNING PENGAMAN BRANKAS BERBASIS IoT MENGGUNAKAN METODE ALGORITMA NAIVE BAYES PADA PLATFORM THING SPEAK - Faritcan Parlaungan Siallagan, Timbo; Alghifari, Muhammad (Jurnal Teknologi Informasi dan Komunikasi, 2023)
A safe is a tool used to store items, including money, jewelry, or other assets and securities. It is claimed to be simple but carries a high risk because it makes it easy for the safe to be broken into without the owner's knowledge. A household assistant (ART) with the initials HS stole a safe from inside her employer's house located in Taman Kedoya Permai, Kebon Jeruk, West Jakarta, "The safe contained securities documents, two house certificates, and several other documents," said Kebon Jeruk Police Chief Commissioner Slamet Riyadi in Jakarta. With this, the author developed by creating a tool entitled "Machine Learning for Safe Security Based on IoT (Internet of Things) Using the Naïve Bayes Algorithm Method on the ThingSpeak Platform" equipped with RFID as safe door access, SW-420 sensors to detect vibrations in the event of a forced break-in. , a Passive Infra Red sensor to detect movement by the user, and an HX-711 Load Cell sensor to measure the volume weight of the safe to obtain 4 parameters, then the data is processed using the Naïve Bayes algorithm. Naïve Bayes is a statistical grouping that can be used to predict the probability of class members. Naïve Bayes also has extreme accuracy and speed when applied to databases with big data.